Influence of Particle Size Distribution of High Calcium Fly Ash on HVFA Mortar Properties - Antoni .; Hendra Surya Wibawa; Djwantoro Hardjito (Institute of Research and Community Outreach - Petra Christian University, 2018)
This study evaluates the effect of particle size distribution (PSD) of high calcium fly ash on high volume fly ash (HVFA) mortar characteristics. Four PSD variations of high calcium fly ash used were: unclassified fly ash and fly ash passing sieve No. 200, No. 325 and No. 400, respectively. The fly ash replacement ratio of the cementitious material ranged between 50-70%. The results show that with smaller fly ash particles size and higher levels of fly ash replacement, the workability of the mixture was increased with longer setting time. There was an increase in mortar compressive strength with finer fly ash particle size, compared to those with unclassified ones, with the highest strength was found at those with fly ash passing mesh No. 325. The increase was found due to better compactability of the mixture. Higher fly ash replacement reduced the mortar’s compressive strength, however, the rate was reduced when finer fly ash particles was used.